Cytotoxic effect of compounds isolated from Goniothalamus marcanii Craib stem barks - K. Thienthiti (2018)
© 2017, Mahidol University - Faculty of Pharmacy. Goniothalamus marcanii Craib (synonym of Goniothalamus tamirensis Pierre ex Finet Gagnep), is locally known as Khao Lam in Thai. The previous study showed that the isolated compounds from stem barks exhibited high cytotoxicity to human tumor cell lines. The objective of the research was to investigate compounds which showed cytotoxic effect. Column chromatography was used for isolation. The structures of the compounds were investigated by spectroscopic methods. The bioactivity of the compounds was determined by SRB assay. The result showed that four compounds, a styryl-lactone: (+)-goniodiol (1); and three alkaloids: ouregidione (2); noraristolodione (3); velutinam (4) were isolated from G. marcanii stem barks. Compound 3 possessed the strongest activity (EC5035.56 and 50.75 μM), for A549 (lung) cells and HeLa (cervix) cells, respectively. Compound 1-3 displayed cytotoxic activity but less than that of doxorubicin, a conventional chemotherapeutic drug, the EC50levels of which were 0.13 and 0.12 μM for A549 and HeLa cells, respectively. On the other hand, compound 2 and 4 which could be evaluated from selective index values (SI 1.25 and 1.70, respectively) showed lower toxicity towards normal cells (MRC5) than doxorubicin (SI = 1.07). From this study, G. marcanii stem barks found to be a new source of compounds 1-4. In addition, the investigation of compound 3 in cytotoxic activity and the evaluation of compounds 1 and 2 for cytotoxic activity to HeLa cell line have been reported for the first time.